Basic strategies for teaching Chamber Music to String Quartets: Training Young Musicians - Flores, José Gerardo (situArte, 1970)
String quartets at the undergraduate level are not very developed musically or technically. Moreover, string players at this stage have not reached the individual technical maturity that they usually have at the graduate level. As the director of the only string quartet in residence at Texas A&M University, Corpus Christi, I have been teaching this kind of students. I have struggled, trying to find literature on the subject of teaching chamber music at a basic level. To date, I have not yet found an outline similar to the one presented here. Concepts such as group tuning, usage of Tartini Tones, sound blend, group pulse and concert preparation are explored and discussed. Other topics include choosing the right repertoire for a young string quartet, recommendations to improve sight-reading and a discussion on how to perform with little preparation. Finally, I present a brief comment on how to guide students to become successful free lancers as chamber musicians. The theoretical framework for this article is based on the book Strategies for Teaching Strings by Hamann and Gilliespie (2009).